Pembelajaran Bahasa Arab Berbasis Rutinitas Harian: Kajian Literatur tentang Strategi Personal Pemula - Mutu Manikam, Manik; Sarimah; Nisa , Fakihatun; Sumiarti; Nopal, Muhammad (Program Studi Pendidikan Bahasa Arab, 2025)
Arabic language learning holds significant urgency in the context of understanding Islamic teachings, as the Qur'an and Hadith—the primary sources of Islam—are conveyed in Arabic. However, learning Arabic as a foreign language often presents challenges for beginners (mubtadi’) due to the complexity of grammar (nahwu and sharf), unique phonetic systems, and substantial linguistic and cultural differences. This study aims to analyze Arabic language learning strategies based on daily routines as an alternative approach that is more contextual and natural. The research employed a library research method by collecting and synthesizing previous studies published between 2020 and 2025. The findings indicate that integrating daily religious routines (daily prayers, dzikir, greetings), social routines (simple conversations and greetings), and learning routines (listening to murottal and writing short journals) effectively strengthens vocabulary, enhances listening skills (maharah istima’) and speaking skills (maharah kalam), and fosters consistent learning habits. Supporting strategies such as self-directed learning (SDL), contextual learning, and natural exposure also play a crucial role in promoting independent and contextualized learning. Nevertheless, these strategies face challenges, including the need for teachers’ creativity, technical skills in utilizing digital media, and learners’ commitment to consistent practice. This study recommends developing humanistic and applicative teaching methods based on daily routines to support Arabic language acquisition for beginners.